A Title I ESEA Case Study Spanish English Developmental Program, Buffalo, New York. - Bureau of Elementary and Secondary Education (DHEW/OE), Washington, DC. Div. of Compensatory Education; Bureau of Elementary and Secondary Education (DHEW/OE), Washington, DC. Div. of Compensatory Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This pamphlet describes the Spanish English Developmental Program, one component of Buffalo's overall Title 1 program. Begun in January, 1970, with funds from New York's Urban Education Act, the program seeks to provide bilingual instruction for nearly 1,600 students of Spanish origin. In August 1970, Title 1 ESEA funds were allocated to cover the cost of the program, and the children involved received other Title 1 services as well. All staff members, including 112 teachers, 33 aides, a social worker, and a guidance counselor, are fluent in both English and Spanish. An orientation course in Puerto Rican culture and history is offered at all Title 1 schools by a floating teacher/aide team. The school system plans to implement a full-year course in Puerto Rican culture and history at the secondary level. The pamphlet contains information on planning, managing, and implementing the program. Also included are data concerning the budget, evaluation, and future plans. (Author/SK)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (Stock Number 1780-1005, $0.35).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Biculturalism; Bilingual Education; Bilingualism; Developmental Programs; English; Ethnic Groups; Ethnic Studies; Evaluation; Minority Groups; Program Descriptions; Puerto Ricans; Spanish; Spanish Speaking; New York (Buffalo)